THE TECHNOLOGICAL PECUHARITIES OF THE STEEL PROCESSING WITH POWDER-LIKE COMPLEX DEOXIDIZING AGENTS ON THE BASIS OF CA + P3M - S. V. Terletskij; A. V. Olenchenko; V. V. Pivtsajev (Литьë и металлургия)
The technological peculiarities of the steel processing with powder-like complex deoxidizing agents on the basis of Ca+P3M are given.